Near‐future forest vulnerability to drought and fire varies across the western United States - Polly C. Buotte; Samuel Levis; Beverly E. Law; Tara W. Hudiburg; David E. Rupp; Jeffery J. Kent (Global Change Biology, 2019)
Recent prolonged droughts and catastrophic wildfires in the western United States have raised concerns about the potential for forest mortality to impact forest structure, forest ecosystem services, and the economic vitality of communities in the coming decades. We used the Community Land Model (CLM) to determine forest vulnerability to mortality from drought and fire by the year 2049. We modified CLM to represent 13 major forest types in the western United States and ran simulations at a 4‐km grid resolution, driven with climate projections from two general circulation models under one emissions scenario (RCP 8.5). We developed metrics of vulnerability to short‐term extreme and prolonged drought based on annual allocation to stem growth and net primary productivity. We calculated fire vulnerability based on changes in simulated future area burned relative to historical area burned. Simulated historical drought vulnerability was medium to high in areas with observations of recent drought‐related mortality. Comparisons of observed and simulated historical area burned indicate simulated future fire vulnerability could be underestimated by 3% in the Sierra Nevada and overestimated by 3% in the Rocky Mountains. Projections show that water‐limited forests in the Rocky Mountains, Southwest, and Great Basin regions will be the most vulnerable to future drought‐related mortality, and vulnerability to future fire will be highest in the Sierra Nevada and portions of the Rocky Mountains. High carbon‐density forests in the Pacific coast and western Cascades regions are projected to be the least vulnerable to either drought or fire. Importantly, differences in climate projections lead to only 1% of the domain with conflicting low and high vulnerability to fire and no area with conflicting drought vulnerability. Our drought vulnerability metrics could be incorporated as probabilistic mortality rates in earth system models, enabling more robust estimates of the feedbacks between the land and atmosphere over the 21st century.

The Benefits of Reduced Anthropogenic Climate changE (BRACE): a synthesis - Brian C. O’Neill; James M. Done; Andrew Gettelman; Peter Lawrence; Flavio Lehner; Jean-Francois Lamarque; Lei Lin; Andrew J. Monaghan; Keith Oleson; Xiaolin Ren; Benjamin M. Sanderson; Claudia Tebaldi; et al. (Climatic Change, 2018)

Avoided economic impacts of climate change on agriculture: integrating a land surface model (CLM) with a global economic model (iPETS) - Xiaolin Ren; Matthias Weitzel; Brian C. O’Neill; Peter Lawrence; Prasanth Meiyappan; Samuel Levis; Edward J. Balistreri; Michael Dalton (Climatic Change, 2018)

CLMcrop yields and water requirements: avoided impacts by choosing RCP 4.5 over 8.5 - Samuel Levis; Andrew Badger; Beth Drewniak; Cynthia Nevison; Xiaolin Ren (Climatic Change, 2018)

On the development of a coupled regional climate–vegetation model RCM–CLM–CN–DV and its validation in Tropical Africa - Guiling Wang; Miao Yu; Jeremy S. Pal; Rui Mei; Gordon B. Bonan; Samuel Levis; Peter E. Thornton (Climate Dynamics, 2016)

Ozone exposure causes a decoupling of conductance and photosynthesis: implications for the Ball-Berry stomatal conductance model - Danica Lombardozzi; Jed P. Sparks; Gordon Bonan; Samuel Levis (Oecologia, 2012)

COSMO-CLM2: a new version of the COSMO-CLM model coupled to the Community Land Model - Edouard L. Davin; Reto Stöckli; Eric B. Jaeger; Samuel Levis; Sonia I. Seneviratne (Climate Dynamics, 2011)

Impact of vegetation feedback on the temperature and its diurnal range over the Northern Hemisphere during summer in a 2 × CO2 climate - Su-Jong Jeong; Chang-Hoi Ho; Tae-Won Park; Jinwon Kim; Samuel Levis (Climate Dynamics, 2011)

Anthropogenic land cover changes in a GCM with surface albedo changes based on MODIS data - Maria Malene Kvalevåg; Gunnar Myhre; Gordon Bonan; Samuel Levis (International Journal of Climatology, 2010)
This study uses a global climate model (GCM) to investigate the climate response at the surface and in the atmosphere caused by land use change. The climate simulations are performed with the National Center for Atmospheric Research Community Land Model 3.5 (CLM3.5) coupled to the Community Atmosphere Model 3 (CAM3) and a slab ocean model. We use the Moderate Resolution Imaging Spectroradiometer (MODIS) surface albedo product to represent surface albedo in the CLM3.5 for both present day and to reconstruct the surface albedo for natural pre‐agriculture conditions. We compare simulations including vegetation changes and surface albedo changes to simulations including only surface albedo changes. We find that the surface albedo change is most dominant in temperate regions while the change in evapotranspiration drives the climate response in the tropics. Our results show that land cover changes contribute to an annual global warming of 0.04 K, but there are large regional differences. In North America and Europe, the surface temperatures decrease by − 0.11 and − 0.09 K, respectively, while in India the surface temperatures increase by 0.09 K. When we fix the vegetation cover in the simulations and let the climate changes be driven only by the differences in surface albedo, the annual global mean surface warming is reduced, and all three regions are now associated with surface cooling. We also show that the surface albedo value for cropland is of major importance in climate simulations of land cover change. The surface albedo effect is the main driving mechanism when the change in surface albedo between agricultural and natural vegetation is substantial. Finally, we argue that differences in the surface albedo value of cropland implemented in earlier land use change studies explain the diversity in the sign and magnitude of the climate response. Copyright © 2009 Royal Meteorological Society

Improvements in a half degree atmosphere/land version of the CCSM - Peter R. Gent; Stephen G. Yeager; Richard B. Neale; Samuel Levis; David A. Bailey (Climate Dynamics, 2010)

Effects of global irrigation on the near-surface climate - William J. Sacks; Benjamin I. Cook; Nikolaus Buenning; Samuel Levis; Joseph H. Helkowski (Climate Dynamics, 2009)

The thermoinsulation effect of snow cover within a climate model - Benjamin I. Cook; Gordon B. Bonan; Samuel Levis; Howard E. Epstein (Climate Dynamics, 2008)

Rapid vegetation responses and feedbacks amplify climate model response to snow cover changes - Benjamin I. Cook; Gordon B. Bonan; Samuel Levis; Howard E. Epstein (Climate Dynamics, 2008)

Combined statistical and dynamical assessment of simulated vegetation–rainfall interactions in North Africa during the mid‐Holocene 1 - MICHAEL NOTARO; YI WANG; ZHENGYU LIU; ROBERT GALLIMORE; SAMUEL LEVIS (Global Change Biology, 2008)
A negative feedback of vegetation cover on subsequent annual precipitation is simulated for the mid‐Holocene over North Africa using a fully coupled general circulation model with dynamic vegetation, FOAM‐LPJ (Fast Ocean Atmosphere Model‐Lund Potsdam Jena Model). By computing a vegetation feedback parameter based on lagged auto‐covariances, the simulated impact of North African vegetation on precipitation is statistically quantified. The feedback is also dynamically assessed through initial value ensemble experiments, in which North African grass cover is initially reduced and the climatic response analyzed. The statistical and dynamical assessments of the negative vegetation feedback agree in sign and relative magnitude for FOAM‐LPJ. The negative feedback on annual precipitation largely results from a competition between bare soil evaporation and plant transpiration, with increases in the former outweighing reductions in the latter given reduced grass cover. This negative feedback weakens and eventually reverses sign over time during a transient simulation from the mid‐Holocene to present. A similar, but weaker, negative feedback is identified in Community Climate System Model Version 2 (CCSM2) over North Africa for the mid‐Holocene.

Soil feedback drives the mid-Holocene North African monsoon northward in fully coupled CCSM2 simulations with a dynamic vegetation model - Samuel Levis; Gordon B. Bonan; Cline Bonfils (Climate Dynamics, 2004)

A dynamic global vegetation model for use with climate models: concepts and description of simulated vegetation dynamics - Gordon B. Bonan; Samuel Levis; Stephen Sitch; Mariana Vertenstein; Keith W. Oleson (Global Change Biology, 2003)
Changes in vegetation structure and biogeography due to climate change feedback to alter climate by changing fluxes of energy, moisture, and momentum between land and atmosphere. While the current class of land process models used with climate models parameterizes these fluxes in detail, these models prescribe surface vegetation and leaf area from data sets. In this paper, we describe an approach in which ecological concepts from a global vegetation dynamics model are added to the land component of a climate model to grow plants interactively. The vegetation dynamics model is the Lund–Potsdam–Jena (LPJ) dynamic global vegetation model. The land model is the National Center for Atmospheric Research (NCAR) Land Surface Model (LSM). Vegetation is defined in terms of plant functional types. Each plant functional type is represented by an individual plant with the average biomass, crown area, height, and stem diameter (trees only) of its population, by the number of individuals in the population, and by the fractional cover in the grid cell. Three time‐scales (minutes, days, and years) govern the processes. Energy fluxes, the hydrologic cycle, and carbon assimilation, core processes in LSM, occur at a 20 min time step. Instantaneous net assimilated carbon is accumulated annually to update vegetation once a year. This is carried out with the addition of establishment, resource competition, growth, mortality, and fire parameterizations from LPJ. The leaf area index is updated daily based on prevailing environmental conditions, but the maximum value depends on the annual vegetation dynamics. The coupling approach is successful. The model simulates global biogeography, net primary production, and dynamics of tundra, boreal forest, northern hardwood forest, tropical rainforest, and savanna ecosystems, which are consistent with observations. This suggests that the model can be used with a climate model to study biogeophysical feedbacks in the climate system related to vegetation dynamics.

Stability Analysis of the Climate-Vegetation System in the Northern High Latitudes - Victor Brovkin; Samuel Levis; Marie-France Loutre; Michel Crucifix; Martin Claussen; Andrey Ganopolski; Claudia Kubatzki; Vladimir Petoukhov (Climatic Change, 2003)

On the stability of the high‐latitude climate‐vegetation system in a coupled atmosphere‐biosphere model - Samuel Levis; Jonathan A. Foley; Victor Brovkin; David Pollard (Global Ecology and Biogeography, 1999)
Summary In order to investigate the hypothesis that the Earth's climate and vegetation patterns may have more than one basic state, we use the fully coupled GENESIS‐IBIS model. GENESIS is an atmospheric general circulation model. IBIS is a dynamic global vegetation model that integrates biophysical, physiological, and ecological processes. GENESIS and IBIS are coupled by way of a common land surface interface to allow for the full and transient interaction between changes in the vegetation structure and changes in the general circulation of the atmosphere. We examine two modern climate simulations of the coupled model initialized with two different initial conditions. In one case, we initialize the model vegetation cover with the modern observed distribution of vegetation. In the other case, we initialize the vegetation cover with evergreen boreal forests extending to the Arctic coast, replacing high‐latitude tundra. We interpret the coupled model's behaviour using a conceptual model for multistability and demonstrate that in both simulations the climate‐vegetation system converges to the same equilibrium state. In the present climate, feedbacks between land, ocean, sea ice, and the atmosphere do not result in the warming required to support an expanded boreal forest.

Coupling dynamic models of climate and vegetation - JONATHAN A. FOLEY; SAMUEL LEVIS; COLIN I. PRENTICE; DAVID POLLARD; STARLEY L. THOMPSON (Global Change Biology, 1998)

Coupling dynamic models of climate and vegetation - Jonathan A. Foley; Samuel Levis; I. Colin Prentice; David Pollard; Starley L. Thompson (Global Change Biology, 1998)
Numerous studies have underscored the importance of terrestrial ecosystems as an integral component of the Earth's climate system. This realization has already led to efforts to link simple equilibrium vegetation models with Atmospheric General Circulation Models through iterative coupling procedures. While these linked models have pointed to several possible climate–vegetation feedback mechanisms, they have been limited by two shortcomings: (i) they only consider the equilibrium response of vegetation to shifting climatic conditions and therefore cannot be used to explore transient interactions between climate and vegetation; and (ii) the representations of vegetation processes and land‐atmosphere exchange processes are still treated by two separate models and, as a result, may contain physical or ecological inconsistencies. Here we present, as a proof concept, a more tightly integrated framework for simulating global climate and vegetation interactions. The prototype coupled model consists of the GENESIS (version 2) Atmospheric General Circulation Model and the IBIS (version 1) Dynamic Global Vegetation Model. The two models are directly coupled through a common treatment of land surface and ecophysiological processes, which is used to calculate the energy, water, carbon, and momentum fluxes between vegetation, soils, and the atmosphere. On one side of the interface, GENESIS simulates the physics and general circulation of the atmosphere. On the other side, IBIS predicts transient changes in the vegetation structure through changes in the carbon balance and competition among plants within terrestrial ecosystems. As an initial test of this modelling framework, we perform a 30 year simulation in which the coupled model is supplied with modern CO 2 concentrations, observed ocean temperatures, and modern insolation. In this exploratory study, we run the GENESIS atmospheric model at relatively coarse horizontal resolution (4.5° latitude by 7.5° longitude) and IBIS at moderate resolution (2° latitude by 2° longitude). We initialize the models with globally uniform climatic conditions and the modern distribution of potential vegetation cover. While the simulation does not fully reach equilibrium by the end of the run, several general features of the coupled model behaviour emerge. We compare the results of the coupled model against the observed patterns of modern climate. The model correctly simulates the basic zonal distribution of temperature and precipitation, but several important regional biases remain. In particular, there is a significant warm bias in the high northern latitudes, and cooler than observed conditions over the Himalayas, central South America, and north‐central Africa. In terms of precipitation, the model simulates drier than observed conditions in much of South America, equatorial Africa and Indonesia, with wetter than observed conditions in northern Africa and China. Comparing the model results against observed patterns of vegetation cover shows that the general placement of forests and grasslands is roughly captured by the model. In addition, the model simulates a roughly correct separation of evergreen and deciduous forests in the tropical, temperate and boreal zones. However, the general patterns of global vegetation cover are only approximately correct: there are still significant regional biases in the simulation. In particular, forest cover is not simulated correctly in large portions of central Canada and southern South America, and grasslands extend too far into northern Africa. These preliminary results demonstrate the feasibility of coupling climate models with fully dynamic representations of the terrestrial biosphere. Continued development of fully coupled climate‐vegetation models will facilitate the exploration of a broad range of global change issues, including the potential role of vegetation feedbacks within the climate system, and the impact of climate variability and transient climate change on the terrestrial biosphere.